Shotgun Metagenomics of Deep Forest Soil Layers Show Evidence of Altered Microbial Genetic Potential for Biogeochemical Cycling - Frey, Beat; Varliero, Gilda; Qi, Weihong; Stierli, Beat; Walthert, Lorenz; Brunner, Ivano (Frontiers in Microbiology, 2022)
Soil microorganisms such as Bacteria and Archaea play important roles in the biogeochemical cycling of soil nutrients, because they act as decomposers or are mutualistic or antagonistic symbionts, thereby influencing plant growth and health. In the present study, we investigated the vertical distribution of soil metagenomes to a depth of 1.5 m in Swiss forests of European beech and oak species on calcareous bedrock. We explored the functional genetic potential of soil microorganisms with the aim to disentangle the effects of tree genus and soil depth on the genetic repertoire, and to gain insight into the microbial C and N cycling. The relative abundance of reads assigned to taxa at the domain level indicated a 5–10 times greater abundance of Archaea in the deep soil, while Bacteria showed no change with soil depth. In the deep soil there was an overrepresentation of genes for carbohydrate-active enzymes, which are involved in the catalyzation of the transfer of oligosaccharides, as well as in the binding of carbohydrates such as chitin or cellulose. In addition, N-cycling genes involved in the degradation and synthesis of N compounds, in nitrification and denitrification, and in nitrate reduction were overrepresented in the deep soil. Consequently, our results indicate that N-transformation in the deep soil is affected by soil depth and that N is used not only for assimilation but also for energy conservation, thus indicating conditions of low oxygen in the deep soil. Using shotgun metagenomics, our study provides initial findings on soil microorganisms and their functional genetic potential, and how this may change depending on soil properties, which shift with increasing soil depth. Thus, our data provide novel, deeper insight into the "dark matter" of the soil.